Effects and Safety of Lumbar Fusion Techniques in Lumbar Spondylolisthesis: A Network Meta-Analysis of Randomized Controlled Trials. Issue 3 (April 2022) - Kang, Yi-No; Ho, Yu-Wan; Chu, William; Chou, Wen-Shiang; Cheng, Shih-Hao
Study Design: Network meta-analysis of randomized controlled trials. Objectives: Lumbar spondylolisthesis is a common indication for spinal fusion. Lumbar interbody fusion (LIF) is popular method to achieve arthrodesis, but previous syntheses usually used head-to-head comparison of 2 surgical methods, and no of them pooled analysis with high-quality. This network meta-analysis of randomized controlled trials was carried out to simultaneously compare fusion techniques in the treatment of lumbar spondylolisthesis. Methods: Three databases were searched for randomized controlled trials (RCTs) on this topic. After critical appraisal, fusion rate, overall adverse events, operative time, Oswestry Disability Index, and pain were extracted for analysis. We conduced network meta-analysis using contrast-based method. Primary outcomes were reported as risk ratio (RR) with 95% confidence interval (CI). Results: Fifteen RCTs (n = 992) met our eligibility criteria. The RCTs treated patients posterolateral fusion (PLF), posterior LIF (PLIF), transforaminal LIF (TLIF), minimally invasive (MIS) TLIF, extreme lateral LIF (XLIF), and circumferential fusion. The pooled estimate showed that circumferential fusion led to significantly higher fusion rate than PLF (RR = 2.15, 95%CI:1.41–3.28), PLIF (RR = 2.11, 95%CI:1.38–3.22), TLIF (RR = 2.13, 95%CI:1.39–3.27), MIS-TLIF (RR = 2.13, 95%CI:1.35–3.35), and XLIF (RR = 2.01, 95%CI: 1.25–3.22). Moreover, circumferential fusion exhibited the best balance in probability between fusion rate and adverse event rate. No evidence showed inconsistency or small-study effect in the results. Conclusions: Collectively, circumferential fusion might be worth to be recommended because it exhibits the best balance between fusion rate and overall adverse event. PLF is still an inferior procedure and requires shorter operative time.